Gender And Language Variation In The Community Of Chlef : The Relevance Of The Community Of Practice Perspective. - Amina Babou (Al-Lisaniyyat)
A plethora of gender research have considered the community of practice (cofp) framework as an analytical tool which serves for a penetrating analysis of variation. In this paper, we strive to move towards a dynamic not static analysis and explore the avenue of how gender is constructed through language. The gist of this paper is to scrutinise the construction of meaning by means of linguistic variation which is part of the individual’s participation in the different networks. We direct a limelight on the community of Chelifian Arabic and Berber speakers. Variation can be considered, de facto, as part of the speaker’s active participation and his/her construction of the social world and himself or herself in that world.